The values of physical education in the education process and personality development of children and adolescents based on selected books published in Poland after 1989 - Foszczyńska, Beata (Health Promotion & Physical Activity, 2018)
The subject of the article is the presentation of the values of physical education in selected books published in Poland in the last thirty years. The values of physical education are very important element of sports pedagogy. They give a new quality to education and occupy a significant place in it. Different values are implemented by sporting activity. It nfluences the formation of proper moral attitudes and socially valuable behaviors, teaches the principles of fair play, conscientiousness, diligence, perseverance, courage, overcoming weaknesses, comradeship, cooperation skills, loyalty, and also helps in resocialization young people. It increases physical fitness and health. The research used the bibliographic, analytical, descriptive and axiological methods and the technique of content analysis guided by the content and interpretation potential of the axiological dominant of books. The interpretation of axiological contents has shown the values of physical education and sport in the education process and the development of the personality of children and adolescents contain in that books.